The Company that Changed Itself R&D and the Transformations of DSM - Rooij, Arjan van (Amsterdam University Press, 2007)
The role of industrial research in the development of the company that sponsors it is an essential question. This book takes up this question in an historical perspective with a case study of the Dutch chemical company DSM, a company that transformed itself three times over the course of its long history. The case study and its analysis offer a fresh perspective on the history of industrial research. Arjan van Rooij works as a researcher at the Eindhoven University of Technology, the Netherlands. This title is available in the OAPEN Library - http://www.oapen.org.